Pulmonary hypertension in pregnancy - Durga, K.; Yuvarajan, S.; Praveen, R.; Maria Selvam, Antonious; ., Yashoda; V., Karthiga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pulmonary hypertension is defined as an increase in mean pulmonary arterial pressure (mPAP) ≥25 mmHg at rest as assessed by right heart catheterisation. Pulmonary hypertension in pregnancy is known to be associated with significantly high morbidity and mortality rate which ranges between 30% and 56%. So during pregnancy, efforts to be made to diagnose common medical ailments that can be complicated by pulmonary hypertension. Bedside 2D Echo and thoracic ultrasound are the strongly recommended in these patients to diagnose early and prevent the devastating complications. Relevant blood investigations need to be sent to diagnose the underlying etiology and to assess the prognosis. Cardiac catheterization is the gold standard investigation of choice for pulmonary hypertension. But it is 1 performed in very few cardiac centres in developing countries. In India diagnosis largely depends on echocardiography. It should be made clear to women at the time of their PAH diagnosis that pregnancy is not recommended due to the high maternal and fetal risks. If a woman with known PHT become pregnant, counselling should be given for therapeutic abortion. If they are willing for therapeutic abortion, it should be done before 22 weeks of gestation. All women with PHT should be initiated on PAH specific therapies (prostanoids, ccbs, phosphodiesterase inhibitors) except endothelin receptor blockers as it is teratogenic. Pregnancy in PAH is difficult to manage and needs mutidisciplanary team. Pregnancy is not recommended in women with PAH and appropriate counselling to be done to the mother and their relatives.